A Note on Climate Change Impact and Adaptation Strategies in North Kordofan State, Sudan - Adam, Yahia Omar; Elsiddig, Elnour Abdalla (University of Khartoum Journal of Agricultural Sciences, 2023)
The study objectives were to explore the climate change impacts experienced based on the perception of rural households and to explain the adaptation strategies for rural households. Primary data were collected using structured interviews, key-informant interviews and field observations. The secondary data were collected from reports. Random sampling technique was applied to select 200 forest-dependent households in Um-Rawaba locality (100 households) and Sheikan Locality (100 households) in North Kordofan. The data were analyzed using the SPSS statistical package. Descriptive statistics was used to identify dominant responses between households. The study results revealed that the households influenced by local climate change based on their perceptions. The main adaptation strategies by the households were assets selling, saving, reliance on social relations, feeding on wild plants, wild fruits, wild animals; and temporary migration.